Effect of Hexavalent Chromium on the WBCs of the Fresh Water Fish, Labeo rohita - Sivakumar, V; Surendran, A; Thatheyus, A.J (Journal of Experimental and Clinical Toxicology, 2020)
Industrial effluents containing heavy metals may reach aquatic systems either through direct discharge or surface runoff and cause damage to aquatic organisms affecting their immune system and health. Hence the present study has been undertaken to observe the effects of hexavalent chromium on the WBCs of the fresh water fish, Labeorohita. WBCs play a major role in the immune response of the fish. For acute toxicity determination, healthy fish were subjected to static bioassays. The 24, 48, 72, and 96hr LC50 values were 50.88, 42.03, 28.09 and 10.87 ppm respectively. The fish were exposed to 0.5, 1, 1.5 and 2 ppm for 20 days. Differential count of WBCs and total WBC count were determined after every five days for twenty days. Lymphocytes exhibited a decline while the other cells and total WBC count exhibited an increase due to hexavalent chromium exposure. The results were subjected to two way analysis of variance.
Keywords: Heavy metals; Fish; WBC count; Chromium; Labeorohita